Identification, characterization and in vitro activity of hypoglycemic peptides in whey hydrolysates from rubing cheese by-product. (February 2023) - Li, Yiyan; Fan, Yaozhu; Liu, Jinglei; Meng, Zishu; Huang, Aixiang; Xu, Feiran; Wang, Xuefeng
Graphical abstract: Highlights: Whey hydrolysates from rubing cheese by-product have α-glucosidase inhibitory activity. Peptides YPVEPF, VPYPQ, and LPYPY were identified in rubing whey hydrolysates. YPVEPF is an amphipathic peptide and interacted with α-glucosidase. YPVEPF had negligible hemolytic activity and promoted glucose consumption in HepG2 cells. YPVEPF is a novel hypoglycemic peptide with potential application in functional foods. Abstract: The by-product of Chinese rubing cheese is rich in whey protein. Whey hydrolysates exhibit good hypoglycemic activity, but which specific peptide components are responsible for this effect have not yet been investigated. Herein, the α-glucosidase inhibitory activity of the ultrafiltered fraction (<3 kDa) of rubing cheese whey hydrolysates was evaluated with the inhibition rate of 37.89 %. In addition, peptide identification was conducted using LC-MS/MS, and three peptides YPVEPF, VPYPQ, and LPYPY were identified. Among these, YPVEPF had higher α-glucosidase inhibitory activity (IC50  = 3.52 mg/mL) and interacted with α-glucosidase via hydrogen bonding and hydrophobic forces. YPVEPF was characterized as an amphipathic peptide rich in antiparallel (50.50 %) and random coil (35.20 %) structures, as well as showed good tolerance to gastrointestinal digestion and incubation under the temperature range of 20–80 °C. Notably, YPVEPF activity increased in the presence of Al 3+ and Fe 3+, as well as within the pH range of 2.0–6.0. Furthermore, YPVEPF had negligible hemolytic activity at a concentration of 1.0 mg/mL, no toxicity at concentrations below 0.5 mg/mL, and significantly promoted glucose consumption in HepG2 cells ( p  < 0.0001). Collectively, these findings indicate the potential of YPVEPF to be used as a novel hypoglycemic peptide in functional foods.